Éducation et territoire : inégalités ou diversité ? - Buisson-Fenet, Hélène; Rey, Olivier (Entretiens Ferdinand Buisson, 2020)
It has long been held that only management at national level is compatible with the equality objectives of the education system in France. This "detachment" of schools from their territories has been called into question over the past forty years. Sociological research has shown, on the one hand, that national uniformity can handle considerable inequalities in the way students are treated. Decentralisation and the priority education policies introduced in the 1980s have, on the other hand, modified the strictly national management of education. This debate is still topical, as shown, for example, by the launch of "educational cities" or the differentiation of universities through "excellence policies". Should territorial diversity be increased or should the national framework be maintained? Tensions always arise with regard to educational decisions taken at either local level or national level. To assess existing knowledge on these issues, this book brings together both researchers specialising in the relationship between education and territories, from rural schools to universities, and education officials, at both national and local levels, who have made a particular contribution to the territorial dimension of education.